Death at an Irish wedding [large type] - Brannigan, Ellie (Brannigan, Ellie. Irish castle mystery, 2025)
Rayne McGrath's efforts to save the rundown family castle she inherited were an epic failure after she accidentally set fire to the tower and tanked the budget. Is the castle haunted, or is she just unlucky? Meanwhile, her cousin, Ciara Smith, is anxiously booking their joint calendar with special events in the hopes of bringing the property around before they lose everything. When a bridalwear client from LA asks Rayne for help as her guest list spirals out of control, Rayne nabs the answer to her prayers. McGrath Castle is the perfect destination for the exclusive and intimate wedding party of heiress Tori Montgomery and her fiancé, heartthrob actor Jake Anderson. But this white veil occasion turns into a nightmare when Tori's best friend's assistant, Tiffany Quick, is found dead. It's feared Tiffany jumped from the tower, but that theory is quickly put in doubt as secrets within the wedding party come to light. And as the villagers protest this new wedding venue venture, Rayne begins to wonder if she will succeed in her endeavour or lose it all.